International Security - Gil, Thomas (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: Originally, international security was conceived in a restrictive sense as national, state, or military security. Different circumstances, events, and the theorizing about them, however, have led to broaden and to deepen the conception of it.